Parkinson’s Disease in Teneurin Transmembrane Protein 4 (TENM4) Mutation Carriers - Pu, Jia-Li; Gao, Ting; Si, Xiao-Li; Zheng, Ran; Jin, Chong-Yao; Ruan, Yang; Fang, Yi; Chen, Ying; Song, Zhe; Yin, Xin-Zhen; Yan, Ya-Ping; Tian, Jun; et al. (Frontiers in Genetics, 2020)
Introduction: Mutations in the teneurin transmembrane protein 4 (TENM4) gene, known to be involved in neuropsychiatric disorders, have been identified in three pedigree of essential tremor (ET) from Spain. ET has overlapping clinical manifestations and epidemiological symptoms with Parkinson’s disease (PD), suggesting these two disorders may reflect common genetic risk factors. In this study, we investigated clinical and genetic manifestations in four unrelated pedigrees with both ET and PD in which TENM4 variants were identified. Methods: We subsequently explored whether TENM4 variants contributed to the risk of developing PD. The frequency of TENM4 variants was evaluated from four PD pedigrees and other 407 subjects. Results: The results revealed 12 different novel heterozygous variants, all at low frequency. A clear general enrichment of TENM4 variants was detected in early-onset PD patients (p < 0.001, OR = 5.264, 95% CI = 1.957-14.158). Conclusion: The results indicate that rare TENM4 variants may be associated with an increased risk of PD.